STUDI DESKRIPTIF MINAT MAHASISWA STT KAO TENTANG PENGEMBANGAN KARUNIA ROH KUDUS DALAM PELAYANAN PEMBERITAAN INJIL - Luhur, Chandra Kirana (Sekolah Tinggi Teologi Kristus Alfa Omega, 2020)
Carrying out the mission of the great commission is a general church task, which must be carried out by all believers. Conducting missions in the 4.0 era is a challenge in itself, and the university must empower the student with the gift of the Holy Spirit who can answer the needs of mission services in this era. The research is a quantitative research, applying descriptive and phenomenological methods to show a description of service needs related to mission in the 4.0 era. As a result, a leader,must first be empowered in terms of gifts so as to optimize the gifts that are in the students.